Analysis of Nanoparticle Additive Couple Stress Fluids in Three-layered Journal Bearing - T. , V. V. L. N. Rao (2012)
This work presents one-dimensional analysis of nanoparticle additive couple stress fluids in three-layered journal bearing. The three-layered film in journal bearing is described through adsorbent layer at surfaces of higher viscosity than core layer. The adsorbent layers and the core layer are modeled using Newtonian and couple stress fluids respectively. The nondimensional pressure and shear stress expressions are derived. Pressure distribution is obtained using Reynolds boundary conditions. The effect of surface adsorbent fluid film layer thickness on nondimensional load capacity and coefficient of friction are analyzed for (i) dynamic viscosity ratio of surface to core; (ii) nanoparticle volume fraction; and (iii) couple stress parameter. The nondimensional load capacity increases with increase in nanoparticle volume fraction in fluid film. An increase in nondimensional load capacity and decrease in coefficient of friction are obtained with increase in (i) surface adsorbent fluid film layer thickness, (ii) dynamic viscosity ratio of surface to core layer and (iii) couple stress parameter.